An assessment on the degree of local government discretion on decision making in urban local authorities: a case study of Kadoma city council - Hapanyengwi, Emeliah (Midlands State University, 2017)
This study sought to assess the degree of local government discretion in decision making in urban local authorities using Kadoma City Council as a case study. The study analysed the powers of urban local authorities and the constraints being faced in fostering quality services. A qualitative research design was used in this assessment. A sample of 40 respondents was chosen. The sample included the mayor, town clerk, councillors, directors, H.O.Ds and employees. Both secondary and primary data were used in the collection of data. Data was collected from interviews, questionnaires and reports from other researchers to come up with conclusions. The study acknowledged that urban local authorities have no autonomous voice regarding decision making and planning issues because of the powers vested upon the Minister and the President. Urban local authorities derives their duties and powers from different acts of parliament that makes local authorities being subordinated to other Ministries for example the Water Act, Road Act , Health Act to mention but a few. Through a survey that the researcher conducted, it indicated that poor revenue base, political interference, undemocratic legislative amendments, poor governance and making of by-laws are some of the constraints that are being faced by KCC. Borrowing powers and laws reforms are suggested mechanisms that the government of Zimbabwe must adopt. Sustainable financing, transparency, integrated planning of sustainable infrastructure and valuing of local skills can enable urban local authorities to steer socio-economic growth.